Microbial competition between Escherichia coli and Candida albicans reveals a soluble fungicidal factor - Damien J. Cabral; Swathi Penumutchu; Colby Norris; Jose Ruben Morones-Ramirez; Peter Belenky (Microbial Cell, 2018)
Localized and systemic fungal infections caused by Candida albicans can lead to significant mortality and morbidity. However, severe C. albicans infections are relatively rare, occurring mostly in the very young, the very old, and immunocompromised individuals. The fact that these infections are rare is interesting because as much as 80 percent of the population is asymptomatically colonized with C. albicans. It is thought that members of the human microbiota and the immune system work in concert to reduce C. albicans overgrowth through competition and modification of the growth environment. Here, we report that Escherichia coli (strain MG1655) outcompetes and kills C. albicans (strain SC5314) in vitro. We find that E. coli produces a soluble factor that kills C. albicans in a magnesium-dependent fashion such that depletion of available magnesium is essential for toxicity.